Association between changes in the triglyceride glucose-body roundness Index and cardiovascular disease risk in middle-aged and elderly Chinese adults: a nationwide longitudinal study from 2011 to 2015 - Yang, Yu; Cao, Jinfeng; Lyu, Jie (Frontiers in Nutrition, 2025)
BackgroundCardiovascular disease (CVD) is a major global health issue. The triglyceride-glucose (TyG) index, a marker of insulin resistance, and the body roundness index (BRI), reflecting visceral adiposity, are key risk factors for chronic diseases. However, research on the long-term impact of changes in obesity and metabolic markers on CVD risk is limited. This study examines the association between long-term changes in the TyG-BRI composite index and CVD incidence in middle-aged and older Chinese adults.MethodsData were obtained from the China Health and Retirement Longitudinal Study, which included 4,446 middle-aged and elderly from 2011 to 2015. The participants were classified into three clusters based on TyG-BRI changes by K-means clustering method. Logistic regression analyses and restricted cubic spline (RCS) regression analyses were used to assess the association between the TyG-BRI and CVD incidence. Receiver operating characteristic (ROC) curves were generated to compare the predictive accuracy of the TyG-BRI, TyG, and BRI.ResultsBy the end of 2015, 1,007 participants (22.6%) had developed CVD. The incidence of CVD increased progressively across TyG-BRI clusters. After adjusting for multiple covariates, logistic regression analysis revealed a significant correlation between the TyG-BRI and the onset of CVD [odds ratio, 95% confidence interval: 1.251 (1.139–1.373) per 1 SD increase]. The RCS regression analysis revealed a significant positive and linear relationship between the TyG-BRI and CVD incidence (P for overall < 0.001, P for nonlinear = 0.874). ROC analysis revealed that the TyG-BRI had greater predictive accuracy for CVD than either BRI or TyG alone did (AUC: 0.678 vs. 0.583 and 0.555, P < 0.001).ConclusionLong-term variations in the TyG-BRI index are closely associated with CVD risk, demonstrating superior predictive performance compared to using BRI or TyG alone. Our findings offer new insights into the interplay between metabolic dysfunction and cardiovascular risk. TyG-BRI may serve as a more effective auxiliary tool for CVD risk assessment and provides valuable guidance for the early identification of high-risk populations.